Acoustically‐Induced Water Frustration for Enhanced Hydrogen Evolution Reaction in Neutral Electrolytes. Issue 7 (4th December 2022) - Ehrnst, Yemima; Sherrell, Peter C.; Rezk, Amgad R.; Yeo, Leslie Y.
Abstract: A novel strategy utilizing high‐frequency (10 MHz) hybrid sound waves to dramatically enhance hydrogen evolution reactions (HER) in notoriously difficult neutral electrolytes by modifying their network coordination state is presented. Herein, the practical limitations associated with existing electrolyzer technology is addressed, including the need for highly corrosive electrolytes and expensive electrocatalysts, by redefining conceptually‐poor hydrogen electrocatalysts in neutral electrolytes. The improvement in HER performance is attributed to the unique capability of the intense local electromechanical coupling arising from the acoustic‐forcing to 'frustrate' the tetrahedrally‐coordinated hydrogen bond network of water molecules at the electrode–electrolyte interface, resulting in the generation of a high concentration of "free" water molecules that are more readily able to access catalytic sites on the unmodified polycrystalline electrode. Together with the other synergistic effects that accompany the acoustic excitation (e.g., hydronium ion generation, convective relaxation of diffusion mass transfer limitations, and prevention of bubble build‐up and their removal from the electrode), the resultant overpotential reduction of 1.4 V at −100 mA cm −2 and corresponding 14‐fold increase in current density, together with a net‐positive energy saving of 27.3%, showcases the potential of the technology as a scalable platform for effectively enhancing the efficiency of green hydrogen production. Abstract : Employing high‐frequency (10 MHz) electroacoustic waves in electrochemistry for the hydrogen evolution reaction (HER) redefines the use of traditionally poor catalysts in challenging neutral conditions. The electroacoustic waves induce "water‐frustration" of the electrolyte coupled with efficient convective mass transport, bubble growth suppression and removal, which together lead to a dramatically enhanced HER rate across various combinations of electrodes and electrolytes.